TARGETED THERAPY OF ANAPLASTIC THYROID CANCER - Kononenko, Mykola; Duzhiy, Ihor; Moskalenko, Yuliia (Eastern Ukrainian Medical Journal, 2023)
Introduction. Anaplastic thyroid cancer is an aggressive disease with meager patient survival. The tumors are often unresectable and insensitive to standard treatment methods (chemotherapy and radioiodine therapy). In recent years, much attention has been paid to new therapeutic strategies, mainly targeted therapy. The purpose of our study was to summarize the data on targeted drugs used to treat anaplastic thyroid cancer and establish the main side effects associated with their use. Materials and methods. A scientific search was conducted in Pubmed, Scopus, and Web of Science databases. The following search terms were used: "anaplastic thyroid cancer," "targeted therapy," and "clinical trials." Results. A literature search was conducted regarding targeted drugs to treat anaplastic thyroid cancer. The results of clinical trials using BRAF/MEK, RET, NTRK, mTOR, and TKI inhibitors were analyzed. Several clinical trials have demonstrated that dabrafenib, combined with trametinib, has a sufficiently high therapeutic effect and can effectively treat anaplastic thyroid cancer. Other targeted drugs show limited clinical response, such as NTRK inhibitors, TKIs, and other BRAF/MEK inhibitors. Some drugs (e.g., lenvatinib) may only be effective with other anticancer agents. RETi and mTORi are believed to have some therapeutic potential, but more than several clinical trials are needed to evaluate their effectiveness. Discussion. The main reason for the relapse of the disease and the ineffectiveness of targeted drugs is the appearance of new mutations. The RAS mutation is responsible for resistance to the combination of dabrafenib and trametinib; the S100A4 protein is responsible for the ineffectiveness of vemurafenib. Developing new drugs capable of overcoming resistance mechanisms is necessary to solve this problem. Conclusions. Targeted therapy is a promising direction in the treatment of anaplastic thyroid cancer. Side effects are common but mostly manageable.